COMBUSTION SIMULATION OF 1kW CLASS LNG STIRLING ENGINE CHP SYSTEM CONSIDERING HEAT RECOVERY - 김혁주; YOUN SIK LEE; 안준 (International journal of air-conditioning and refrigeration, 2013)
As fossil fuel has been depleted, a reasonable use of energy is required. In this regard, the cascade use of thermal energy has been proactively considered in view of available energy. For the purpose,the micro co-generation system for a household based on Stirling engine was suggested as a unit of distributed energy system. A slot-type premixed burner is used to completely block noises and harmful gases for the purpose of use in a household, and air supplied to a burner recovers heat from the exhaust gas in order to improve the e±ciency of energy use. This study conducted a numerical simulation on combustion in a combustion chamber to investigate the e®ects that recuperation of heat from exhaust gas have on heat transfer and combustion characteristics. KCI Citation Count: 2